Entrustable Professional Activities in Hematopathology Pathology Fellowship Training: Consensus Design and Proposal - Kristie White MD, MAEd; Julianne Qualtieri MD; Elizabeth L. Courville MD; Rose C. Beck MD, PhD; Bachir Alobeid MD; David R. Czuchlewski MD; Julie Teruya-Feldstein MD; Lorinda A. Soma MD; Sonam Prakash MD; Dita Gratzinger MD, PhD (Academic Pathology, 2021)
Hematopathology fellowship education has grown in complexity as patient-centered treatment plans have come to depend on integration of clinical, morphologic, immunophenotypic, molecular, and cytogenetic variables. This complexity is in competition with the need for timely hematopathology care with stewardship of patient, laboratory, and societal resources. Accreditation Council for Graduate Medical Education Milestones provide a guidance document for hematopathology training, but fellows and their educators are in need of a simple framework that allows assessment and feedback of growth toward independent hematopathology practice. Entrustable professional activities provide one such framework, and herein, we provide proposed Hematopathology Fellowship Entrustable Professional Activities based on review of pertinent guidelines and literature, with multiple rounds of expert and stakeholder input utilizing a modified mini-Delphi approach. Ten core entrustable professional activities deemed essential for graduating hematopathology fellows were developed together with skills and knowledge statements, example scenarios, and corresponding Accreditation Council for Graduate Medical Education Milestones. Application of these entrustable professional activities in program design, fellow evaluation, and decisions regarding level of supervision is discussed with consideration of benefits and barriers to implementation. These entrustable professional activities may be used by hematopathology fellowship directors and faculty to provide fellows with timely constructive feedback, determine entrustment decisions, provide the Clinical Competency Committee with granular data to support Milestone evaluations, and provide insight into areas of potential improvement in fellowship training. Fellows will benefit from a clear roadmap to independent hematopathology practice with concrete and timely feedback.